2018
DOI: 10.1080/19336950.2018.1454814
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic targeting of endothelial Ca2+-activated K+ channels: A strategy to improve cardiovascular function

Abstract: Endothelial small and intermediate-conductance, Ca2+-activated K+ channels (KCa2.3 and KCa3.1, respectively) play an important role in the regulation of vascular function and systemic blood pressure. Growing evidence indicates that they are intimately involved in agonist-evoked vasodilation of small resistance arteries throughout the circulation. Small molecule activators of KCa2.x and 3.1 channels, such as SKA-31, can acutely inhibit myogenic tone in isolated resistance arteries, induce effective vasodilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 86 publications
1
10
0
Order By: Relevance
“…Similar observations have also been reported in murine cremaster muscle arterioles [16] and carotid arteries [13] where SKA-31-induced EDH was wholly dependent on K Ca 3.1 activation. In agonist-induced EDH responses and in vasodilation of resistance arteries induced by Ach, K Ca 3.1 was the predominant K Ca channel reportedly involved [7,11,12,47]. However, our results are in opposition to the findings that K Ca 2.3 plays the main role in the EDH-mediated response in superior mesenteric arteries in SHRSP [38] and in SMAs of angiotensin II-induced hypertension and in SHR [45,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations have also been reported in murine cremaster muscle arterioles [16] and carotid arteries [13] where SKA-31-induced EDH was wholly dependent on K Ca 3.1 activation. In agonist-induced EDH responses and in vasodilation of resistance arteries induced by Ach, K Ca 3.1 was the predominant K Ca channel reportedly involved [7,11,12,47]. However, our results are in opposition to the findings that K Ca 2.3 plays the main role in the EDH-mediated response in superior mesenteric arteries in SHRSP [38] and in SMAs of angiotensin II-induced hypertension and in SHR [45,48].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological activation of the K Ca 3.1 and K Ca 2.3 channels could improve endothelium dysfunction and BP regulation thereby representing novel targets for antihypertensive drugs [10,11,12]. The K Ca 3.1 and K Ca 2.x channel activator SKA-31 (naphtho (1,2-d)thiazol-2-ylamine) exhibits excellent pharmacokinetic properties such as long half-life (12 h), no toxicity, and low plasma protein binding in rodents [13].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have reported that endothelium-dependent, agonist-evoked vasodilation can be augmented in the presence of a low or threshold concentration of a KCa channel activator, such as SKA-31 [28,32,33]. This treatment strategy can further mitigate endothelial dysfunction associated with type 2 diabetes [28,33] and we speculate that it occurs via a pharmacological “priming” or sensitization of endothelial KCa channel activity and EDH-type signaling [53]. In small mesenteric arteries from both SHRs and Wistar rats, SKA-31 treatment augmented ACh, but not BK, induced vasodilation (Figure 1), consistent with the putative sensitization of this GPCR signaling pathway in these vessels.…”
Section: Discussionmentioning
confidence: 72%
“…The K Ca channels are important effectors in the control of vascular tone and blood pressure [ 33 ]. They mediate membrane hyperpolarization in response to elevations of intracellular Ca 2+ and thus counteract SM contractility [ 34 ].…”
Section: Diversity Of K + Channels In Huamentioning
confidence: 99%